An Exploration of Lebanese Leadership Effects on Followers‘ Work and Home Life Integration – A Banking Sector Study - Hachem, Fadi (Cranfield University, 2014)
This thesis examines leaders‘ behaviours differential effects on the work/home balance of their followers through a leader/follower fit perspective. The study explores perceived effects of leader‘s actions on followers‘ work/home balance in a Lebanese context. At the individual/dyad level, this research attempts to integrate these two areas of study. It aims to better understand, Lebanese employees‘ perspectives on the Lebanese leaders‘ practice of leadership in the banking industry and the perceived effect of this practice on the followers‘ work and home boundary management. Based on the adoption of a qualitative exploratory approach, the author conducts thirty semi-structured interviews with five leaders and twenty-five followers in different regions and divisions of the XYZ bank. The dissertation makes several theoretical and empirical contributions. First, boundary theory is empirically extended through the identification of one of the antecedents, i.e., polychronicity, of an individual‘s work/home segmentation/integration preference. Second, boundary theory is developed through the exploration of the Lebanese leaders‘ actions‘ impact on the followers‘ management of their work/home boundaries. Third, the literature on fit between the leader and the follower along different dimensions of interest to them is extended and developed. Fourth, the literature on the Middle East and in Lebanon on specific is enhanced. The implications of the Lebanese context, subject of this study, on the leadership and work/home literature are meaningful. In addition to these contributions, this study helps to surface ―actionable knowledge‖ on how to facilitate an employee‘s struggle to reach a harmony between his work and home life. This search for balance is increasingly sought nowadays as a result of the increase in work-related pressures especially for dual-earners.
Keywords: Leadership Practice; Boundary Theory; Fit Theory; Lebanon; Banking